False consciousness and class struggle in Kate Chopin’s A Pair of Silk Stockings: A Marxist-feminist framework - Ari Wijaya; Rizky Arif Afandi; Zanuar Barep Prasetyo; Rifki Aditia Novaldi (Journal Albion : Journal of English Literature, Language, and Culture, 2026)
This study explores Kate Chopin’s A Pair of Silk Stockings (Chopin, 1996) through the lens of Marxist literary criticism, emphasizing class struggle, commodity fetishism, and alienation in the capitalist social order. The story’s protagonist, Mrs. Sommers, experiences a brief encounter with consumer pleasure after purchasing luxury goods, which reflects both resistance to and entrapment within capitalist ideology. By integrating Marx’s concepts of false consciousness and material determinism with contemporary Marxist-feminist frameworks on social reproduction (Quick, 2023; Rey-Araújo, 2024), this study interprets Mrs. Sommers’s actions as symptomatic of gendered economic subjugation. This research using textual analysis with Marxist framework, the paper reveals how consumption operates as a false form of liberation within the constraints of class and patriarchal capitalism. The findings demonstrate that Chopin’s story, though written in the nineteenth century, anticipates critical concerns of modern Marxist discourse on ideology, labor, and commodified desire. The emotional function of consumption as a false form of liberation continues to characterize modern consumer societies.